North Atlantic Oscillation (NAO) and precipitation in Galicia (Spain) - R. Nieto (Atmósfera, 2005)
In this study we investigate the time-scale at which NAO and ENSO are associated with the precipitation inGalicia (Northwestern of Spain), looking for possible climate predictors. The existence of preferred frequenciesin all series was analyzed by using SSA (Singular Spectral Analysis), whereas the statistical significanceof the results was checked by using the Monte-Carlo method. Results suggest that NAO and precipitation inGalicia could be related at a time scale of 8 years whereas the influence of ENSO is not significant.